Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.46497/archrheumatol.2022.9015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diet, oxidative stress, and inflammation in ankylosing spondylitis

Abstract: Objectives: This study aims to investigate the relationship between disease activity, dietary phytochemical index (DPI), and serum total oxidant status (TOS) and total antioxidant status (TAS) in patients with ankylosing spondylitis (AS). Patients and methods: Between August 2020 and January 2021, a total of 37 patients (23 males, 14 females; mean age: 39.3±9.4 years; range, 21 to 61 years) with AS and 36 age-, sex-, and body mass index-matched healthy individuals (24 males, 12 females; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…12 In a similar study on AS patients, TAC decreased significantly compared to healthy controls, whereas the AS patients exhibited no variation in the total oxidant status (TOS). 13 The current study revealed a decline in the levels SOD in RA and AS compared to the controls, whereas MDA levels was significantly raised in both groups compared to the controls. The outcome was consistent with earlier findings among newly-diagnosed RA patients who had not received any treatment.…”
Section: Discussionsupporting
confidence: 47%
“…12 In a similar study on AS patients, TAC decreased significantly compared to healthy controls, whereas the AS patients exhibited no variation in the total oxidant status (TOS). 13 The current study revealed a decline in the levels SOD in RA and AS compared to the controls, whereas MDA levels was significantly raised in both groups compared to the controls. The outcome was consistent with earlier findings among newly-diagnosed RA patients who had not received any treatment.…”
Section: Discussionsupporting
confidence: 47%
“…TNF-α, IL-6, IL-8, and IL-17 have been identified to be overexpressed in AS patients [34]. Furthermore, in AS patients, neutrophils are activated so that reactive oxygen species are generated, resulting in oxidative stress [35]. Naringin represses AS progression via inhibiting inflammation and oxidative stress in mice [36].…”
Section: Discussionmentioning
confidence: 99%
“…Adıgüzel et al [19] found that patients with AS had lower serum total antioxidant status (TAS) levels and higher oxidative stress index (OSI) scores than healthy individuals. However, there was no significant difference in total oxidant status (TOS) between the two groups.…”
Section: Discussionmentioning
confidence: 99%